Dualism Regulating Requirements for Filling in the Directors of Regional Owned Enterprises in the Regional Government Law and the Limited Liability Company Law - Febriansyah, Wendy (Hang Tuah Law Journal, 2023)
The problem of conflicting norms is a conflict between one regulation and another, such as in regulating the requirements for filling the board of directors of Regional Owned Enterprises. Government Regulation Number 54 of 2017 concerning Regional Owned Enterprises and Regulation of the Minister of Home Affairs Number 37 of 2018 concerning the Appointment and Dismissal of Members of the Supervisory Board or Members of Commissioners and Members of the Board of Directors of Regional Owned Enterprises on the one hand implies the provision of minimum and maximum age requirements for filling Regional Owned Enterprises directors and the selection mechanism through a Selection Committee formed by the Regional Head, while on the other hand Law Number 40 of 2007 concerning Limited Liability Companies determines the absence of age. This study aims to analyze and describe the problems of dualism in the regulation of the terms and mechanisms for filling Regional Owned Enterprises directors and the legal implications of violating the provisions of Law Number 23 of 2014 concerning Regional Government and its various implementing regulations. Based on the type of normative research with a statutory and conceptual approach, this research argues that the terms and mechanisms for filling the Regional-Owned Enterprises directors refer to the regime of the Local Government Law along with all its implementing regulations and the legal consequences of filling the directors who violate the statutory provisions are null and void.